The cetacean offal connection: Feces and vomits of spinner dolphins as a food source for reef fishes - Sazima, Ivan; Sazima, Cristina [UNESP]; Silva Jr., José Martins (My University, 2003)
At Fernando de Noronha Archipelago, southwest Atlantic, reef fishes associated with spinner dolphins (Stenella longirostris) were recorded when the cetaceans congregated in a shallow inlet. In the reef waters the dolphins engaged in several behaviors such as resting, aerial displays and other social interactions, as well as eliminative behaviors such as defecating and vomiting. Twelve fish species in seven families were recorded feeding on dolphin offal. The black durgon (Melichthys niger) was the most ubiquitous waste-eater, and its group size was positively and significantly correlated with dolphin group size. The durgons recognized the postures a dolphin adopts prior to defecating or vomiting, and began to converge to an individual shortly before it actually voided. Offal was quickly fed upon, and the fishes concentrated in the area occupied by the dolphins until the latter left the shallows. Since all the recorded offal-feeding species feed on plankton or drifting algae, feeding on cetacean droppings may be regarded as a switch from foraging on drifting organisms to foraging on drifting offal, a predictable food source in the inlet. Further instances of this cetacean-fish association are predicted to occur at sites where these mammals congregate over reefs with clear water and plankton-eating fishes.